Studi Perilaku Dinding Geser Pelat Baja Bergelombang dengan Penambahan Wall Opening akibat Beban Siklik - Alif Agtif Riyanto; Lalu Samsul Aswadi; Dwi Sat Agus Yuwana (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2025)
Corrugated Steel Plate Shear Wall (CSSW) is an effective solution to enhance the seismic resistance of steel building structures. The design and specification of CSSW need careful optimization to maximize its performance, particularly in reducing lateral forces during an earthquake. This study utilizes the Finite Element Method (FEM) with Abaqus software to assess the ductility and energy dissipation values of various CSSW specimens. The variations tested include plate thickness, plate width, and wave inclination angle, with each variation involving three specimens. A 10% wall opening area is added to evaluate its impact on structural performance. Cyclic loading is applied following the ATC-24 protocol (ATC, 1992). The results indicate that specimens CSSW 2, CSSW 5, and CSSW 8 show the highest ductility values, 29.15, with specifications of 10 mm plate thickness, 3 m plate width, and 45° wave inclination angle. The largest energy dissipation value was observed in CSSW-4, at 6101 kNm, with a 10 mm plate thickness, 1.5 m plate width, and 45° wave inclination angle. This study provides valuable insights for designing more efficient and optimized CSSW for earthquake-resistant steel building structures.